2008
DOI: 10.1080/13561820701722808
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the coin – General Practitioners' experience of working in multidisciplinary teams

Abstract: Multidisciplinary teamwork, defined as the collaboration between different professional groups to achieve a common purpose, is commonly regarded as a means to meet the complex tasks that medicine has to deal with today. However, many attempts to introduce the method in primary care have failed and this is supposed to be partly due to the fact that general practitioners (GPs) did not participate in the implementation of the method. The aim of this investigation was to get a deeper understanding of their attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Consistent with studies elsewhere, 5,24,25 the barriers to collaborative primary care teamworking identified in this study are multiple. Barriers both in New Zealand and other developed countries can be political, organisational, educational, or cultural.…”
Section: Comparison With Existing Literaturesupporting
confidence: 75%
“…Consistent with studies elsewhere, 5,24,25 the barriers to collaborative primary care teamworking identified in this study are multiple. Barriers both in New Zealand and other developed countries can be political, organisational, educational, or cultural.…”
Section: Comparison With Existing Literaturesupporting
confidence: 75%
“…It is likely that primary care teams would benefit from targeted exploration of the skills and services within each team and agreement between all the team members on appropriate patient care pathways within primary care. Failure of previous attempts to introduce multidisciplinary teams in primary care has been partly attributed to the fact that general practitioners did not participate in the implementation of the method [1]. In this study, a consultation with a female participant was twice as likely as a consultation with a male participant to produce a referral (Relative risk = 2.01, 95% Confidence interval = 1.63-2.47).…”
Section: Discussionmentioning
confidence: 67%
“…Multidisciplinary teamwork, defined as the collaboration between different professional groups to achieve a common purpose, is commonly regarded as a means to meet the complex tasks that medicine has to deal with today [1]. Primary care is the appropriate setting to meet 90-95% of all health and personal social service needs [2].…”
Section: Introductionmentioning
confidence: 99%
“…4,7,10,11 To enhance the contribution of health teams in reducing the magnitude of a disease or improving the quality of life of people, it is of utmost importance to have the right 'mix' of health personnel with clear roles and sufficient freedom to exercise their skills. 2,12 Furthermore, implementation of other strategies has also been recommended (such as selecting a good leader 2 ; scientific and rationale decision to decide members of health team based on health concern 6,8 ; organizing training sessions for the members of the health team 1,7 ; ensuring effective interprofessional collaboration 13,14 ; facilitating regular interaction and feedback on performance 12 ; extending adequate infrastructure support 11,12 ; and encouraging research activities to promote better understanding among members of the team at different levels 14 ) in order to expand the benefits of the health team.…”
Section: Concept Of Health Team In Ensuring Universal Health Care Delmentioning
confidence: 99%